An organocatalytic route to 2-heteroarylmethylene decorated N-arylpyrroles - Jean, Alexandre; Blanchet, Jérôme; Rouden, Jacques; Maddaluno, Jacques; De Paolis, Michaël (Beilstein Journal of Organic Chemistry, 2013)
A concise and regioselective preparation of 2-heteroarylmethylene decorated N-arylpyrroles is described through a metal-free Mannich/Wittig/hydroamination sequence followed by isomerization of the N-arylpyrrolidine adducts. Furthermore, the C–H regioselective oxidation of these substrates is demonstrated, extending the molecular diversity and versatility of these scaffolds.
Keywords: C–H oxidation; isomerization; N-arylpyrrole; organocatalysis